POLICIES AIMED AT ENHANCING FINANCIAL INCLUSION DURING A PANDEMIC: A LITERATURE REVIEW - Petighin, Serghei (Economy and Sociology, 2024)
This study examines the financial inclusion policies during pandemics, particularly focusing on their efficacy within emerging economies and areas dominated by informal sectors. The urgency and relevance of the topic are underscored by the heightened economic vulnerabilities these regions face during global health crises, such as the COVID-19 pandemic, which starkly amplify the necessity for robust financial inclusion to uphold economic resilience. The primary objectives of this paper are twofold: firstly, to critically assess the array of financial inclusion policies deployed during pandemics, and secondly, to pinpoint potential policy enhancements informed by contemporary research alongside successful international implementations. Employing a mixed-methods approach, the research synthesizes quantitative data on policy outcomes with qualitative insights from policy analyses and stakeholder interviews. This methodology allows for a nuanced understanding of the multifaceted impacts of financial inclusion initiatives and their adaptability to crisis conditions. Key findings highlight the pivotal role of digital financial services, effective public-private collaborations, and the establishment of adaptive social support mechanisms in promoting financial inclusivity amidst pandemic-induced economic disruptions. These strategies emerge as crucial levers for advancing financial inclusion, providing valuable lessons for crafting policies that are resilient, targeted, and capable of fostering sustainable economic growth and stability in the face of ongoing and future global challenges. The study's insights offer critical guidance for policymakers and financial institutions seeking to enhance financial inclusion frameworks, thereby contributing to the development of more inclusive, equitable, and resilient financial ecosystems worldwide.